Sustainability, Digital Transformation and Fintech: The New Challenges of the Banking Industry - Andrea Pérez (MDPI, 2021)
In the current competitive scenario, the banking industry must contend with multiple challenges tied to regulations, legacy systems, disruptive models/technologies, new competitors, and a restive customer base, while simultaneously pursuing new strategies for sustainable growth. Banking institutions that can address these emerging challenges and opportunities to effectively balance long-term goals with short-term performance pressures could be aptly rewarded. This book comprises a selection of papers addressing some of these relevant issues concerning the current challenges and opportunities for international banking institutions. Papers in this collection focus on the digital transformation of the banking industry and its effect on sustainability, the emergence of new competitors such as FinTech companies, the role of mobile banking in the industry, the connections between sustainability and financial performance, and other general sustainability and corporate social responsibility (CSR) topics related to the banking industry. The book is a Special Issue of the MDPI journal Sustainability, which has been sponsored by the Santander Financial Institute (SANFI), a Spanish research and training institution created as a collaboration between Santander Bank and the University of Cantabria. SANFI works to identify, develop, support, and promote knowledge, study, talent, and innovation in the financial sector
Keywords: 650; stimulus-response model; utilitarian value; Hedonic value; salesperson selling behaviors; customer satisfaction; loan expansion; GDP; NPL; ARDL; VECM; Johansen test of co-integration; unit root; non-performing loans; sovereign debt distress; tail dependence; gaussian copula regression; mobile financial services (MFS); trust; perceived risk; structural equation modeling (SEM); multiple-criteria decision-making (MCDM); technique for order preference by similarity to ideal solution (TOPSIS); analytic hierarchy process (AHP); data envelopment analysis; commercial banks; product innovation; performance evaluation; innovation risk; digital financial inclusion; risk-coping ability; vulnerability to poverty; instrumental variable estimation; emotional intelligence; work-family conflict; job burnout; employees' turnover intention; perceived organizational support; the Vietnamese banking industry; stochastic DEA; multi-attribute decision making; ordinal variable; cross-efficiency; corporate social responsibility disclosure (CSRD); financial performance; Islamic Banking Industry of Pakistan; GRI; AAOIFI; CSRD index; cost of equity; IFRS adoption; European banks; corporate governance; banking regulation; CSP-CFP relationship; banking sustainability; glass ceiling; board composition; equal opportunity policy; CSR; communication; discourse; exposition; narrative; storytelling; banking; catering; utilitarian service; hedonic service; sustainable finance; sustainable financial products; sustainable banking; SDGs; sustainable development; Latin America; ESG.; digital transformation; knowledge management; digital government; public sector; public administration; peer-to-peer lending; bank risk; insolvency risk; illiquidity risk; financial inclusion; vulnerable rural areas; sustainable solutions; central bank digital currency; social sustainability; pharmacy network; sustainable access to cash; nonperforming loans; macroeconomic factors; econometric model; exchange rate; unemployment rate; inflation rate; MoM(micro-operating mechanism); regulatory sandbox